2020
DOI: 10.1088/1742-6596/1613/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Students’ mathematical proficiency in solving calculus problems after Maple implementation

Abstract: This research aimed to analyze and explore the capability of mathematical proficiency second semester math education students of Faculty of Teacher Training and Education (FKIP) Khairun University academic year 2017/2018. In this study mathematical problems are presented in Calculus, and given the opportunity for students to understand the problems provided both from the theoretical aspects related to indicators of mathematical proficiency namely conceptual understanding, procedural fluency, strategic competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…However, in the scientific literature, studies testing these theoretical assumptions provide inconsistent findings. Several studies provide findings stating the superiority of the CBML group (e.g., Ishartono et al, 2022;Jelatu et al, 2018;Kariadinata et al, 2019;Ningsih & Paradesa, 2018;Nurjanah et al, 2020;Takači et al, 2015), whereas other studies have found that CBML implementation does not outperform the group that does not use it (e.g., del Cerro Velázquez & Morales Méndez, 2021;Hamid et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the scientific literature, studies testing these theoretical assumptions provide inconsistent findings. Several studies provide findings stating the superiority of the CBML group (e.g., Ishartono et al, 2022;Jelatu et al, 2018;Kariadinata et al, 2019;Ningsih & Paradesa, 2018;Nurjanah et al, 2020;Takači et al, 2015), whereas other studies have found that CBML implementation does not outperform the group that does not use it (e.g., del Cerro Velázquez & Morales Méndez, 2021;Hamid et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Berikut hasil menelusuri artikel-artikel yang direview menggunakan aplikasi publish and perish dengan kata kunci yang digunakan dapat dilihat pada tabel 1. (Hamid et al, 2020) Pembelajaran berbantuan Maple layak untuk diterapkan sebagai alternatif model pembelajaran Kalkulus untuk meningkatkan kemampuan kemahiran matematis pada siswa dengan keterampilan awal (tinggi, sedang, dan rendah). 9 (Junpeng et al, 2020) Penelitiannya menemukan alat validasi untuk untuk mengukur mathematical proficiency seorang siswa.…”
Section: Hasil Dan Diskusiunclassified
“…Maple has been incorporated into project-based learning for calculus class [27]. The software's implementation in the calculus classroom has been arguably positive [28][29][30][31]. Even though many teachers and college instructors have struggled with delivering online teaching during the COVID-19 pandemic, an initiative from Italy has borne a fruitful resolution by combining Maple with Moodle, a digital learning environment.…”
Section: Teaching With Technologymentioning
confidence: 99%
“…Hamid et al [30] Integral calculus Purnomo et al [31] Multivariable calculus Fissore et al [32] Contextualized problems…”
Section: Maplementioning
confidence: 99%